How Qualitative Research Informs Clinical and Policy Decision Making in Transplantation: A Review. Issue 9 (September 2016) - Tong, Allison; Morton, Rachael L.; Webster, Angela C.
Abstract : Abstract: Patient-centered care is no longer just a buzzword. It is now widely touted as a cornerstone in delivering quality care across all fields of medicine. However, patient-centered strategies and interventions necessitate evidence about patients' decision-making processes, values, priorities, and needs. Qualitative research is particularly well suited to understanding the experience and perspective of patients, donors, clinicians, and policy makers on a wide range of transplantation-related topics including organ donation and allocation, adherence to prescribed therapy, pretransplant and posttransplant care, implementation of clinical guidelines, and doctor-patient communication. In transplantation, evidence derived from qualitative research has been integrated into strategies for shared decision-making, patient educational resources, process evaluations of trials, clinical guidelines, and policies. The aim of this article is to outline key concepts and methods used in qualitative research, guide the appraisal of qualitative studies, and assist clinicians to understand how qualitative research may inform their practice and policy. Abstract : In a quantitative world this paper considers why and how qualitative research provides value in the field of transplantation, both for the clinician and the policy analyst the question is "what is the question?"